สัจนิยมแนววิทยาศาสตร์ : ทฤษฎีความรู้สำหรับสังคมศาสตร์ - มนัสสุรกุล, สาธิต (วารสารสังคมศาสตร์และมนุษยศาสตร์ มหาวิทยาลัยเกษตรศาสตร์, 2017)
Scientific Realism : Epistemology for Social Science Social science research approaches have been greatly influenced by philosophy of natural science. Since 1970s, however, social research based on logical positivism, developed from natural world studies, has been challenged by Hermeneutics on issues of whether and how research on social world should be compatible with logical positivism. This debate leads to the questions of 'On which epistemology should social science be based?' and 'Whether or not should social scientists do their research using philosophy of natural science?'. Alternatively, ùShould social scientists blend the two theories of science?', and in so doing, 'How can social scientists develop the new one?'. The author argues that social science research should be based on scientific realism. This philosophy of science improves some limitations of logical positivism, and accommodates Hermeneutics in some degrees.